Scandiavian children’s literature – tradition and innovation - Mihaylova, Nadezhda; Gospodinova, Antonia (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2022)
The choice of the topic of the present paper is connected with the seventy-fifth anniversary of the creation of “Pippi Longstocking” by Astrid Lindgren, which was translated into more than 70 languages. The aim of the paper is to outline the tradition of Scandinavian children’s literature, focusing on the storytelling mastery of Hans Christian Andersen, Peter Christen Asbjørnsen, Jørgen Moe, Selma Lagerlöf and Astrid Lindgren – pioneers and innovators in the genre of the fairy tale, stories and novels for children not only in the Scandinavian north, but also in the world. The specific literary devices, means of expression, themes, choice of literary characters and imagery in these authors’ literary works are the object of study and are referred to as the basis for the development of Scandinavian literature today.
Keywords: Scandinavian children’s literature